Interactive problem solving: exploring the potential of minimal complex systems - Greiff, Samuel; Funke, Joachim (The nature of problem solving, 2017)
Interactive problem solving (IPS) is considered an increasingly important skill in professional and everyday life as it mirrors the interaction of a human user with dynamic technical and non-technical devices. Here, IPS is defined as the ability to identify the unknown structure of artefacts in dynamic, mostly technology-rich, environments to reach certain goals. Two overarching processes, the acquisition of knowledge and its application, can be theoretically distinguished and this chapter presents two measurement approaches assessing these processes: MicroDYN and MicroFIN, both of which rely on the idea of minimal complex systems (MICS). Whereas MicroDYN models quantitative connections between elements of a problem (i.e. more and less), MicroFIN models qualitative connections between them (e.g. on/off or white/black). This chapter summarises research on these approaches and discusses the implications for educational assessment.